(untitled) (Revista Contexto & Educação, 2022)
The objective of this study is to investigate the relation between foreign language (FL) teachers’ practices and the students’ processes of (re)signification. In order to reach the objective, this research seeks to analyze what practices of (re)signification public school FL teachers understand to adopt in their classroom and in what manner their practices work with the concept of signification through discourse in a FL. The methodology featured a questionnaire of FL teaching practices with 31 multiple choice questions and nine semi-open questions. The questionnaire had the participation of 50 FL teachers from different Brazilian states. The results point to a strong awareness from the teachers about the importance of social interaction in the classroom. The collected data also indicate that the teachers provide the contact with different signification and identification procedures to their students and have a clear concern with students’ social participation and well-rounded education as well. In conclusion, the dialogue with the teachers shows parallels with the teaching and learning theories that work with discourse in the class.